Larvicidal Flavanone and Sesquiterpenes from Goniothalamus macrophyllus (Annonaceae) - Lee, G.C.; Ng, K.N.; Rahmani, M.; Taufiq-Yap, Y.H. (Asian Journal of Chemistry, 2010)
Bioassay-directed fractionation of the stem bark of Goniothalamus macrophyllus allowed for the isolation of two styrylpyrones (+)-goniothalamin (1) and (+)-goniothalamin epoxide (2), one flavanone (-)-pinocembrin (3) and a mixture of essential oils which comprises mainly an inseparable mixture of sesquiterpenes (4). The structures of these compounds were established by spectral data. (3) and (4) have not been reported to be present in this plant. Also, larvicidal activities have not been reported for this plant.